Brachytherapy of prostate carcinoma - Wronczewski, Andrzej; Wronczewska, Anna; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2000)
Brachytherapy is a type of radiation therapy in which radioactive sources are implanted directly into a malignant tumor. It is one of the oldest methods of treatment of prostate carcinoma. It has been developed in the last few years as some new kinds of radioactive isotops, computed system of treatment planning, afterloading technic and transperineal way of radioactive sources implantation into the prostate tissue have been introduced. Significant improvment of treatment results and decrease in complication rate was achieved due to these technics. Treatment results in permanent brachytherapy of prostate cancer in stage A and B can be comperable with those obtained after radical prostatectomy. Morever brachytherapy combined with external beam radiation therapy in stage C allows to improve treatment results in significant way.